Role Of Disspro And Cbsp On Current Seed Supply Situation In Nepal - Pokhrel, Suroj (Journal of Agriculture and Environment, 2013)
The seed replacement rate of major field crops is very low, about 8%, in Nepal with 92% seed supply of major field crops from informal sector. Different seed production initiatives are undertaken by public and private sectors. However, their role and effectiveness on seed sector development have not been assessed. A review on secondary data related to seed production and usage and primary data collected from different public and private organizations in the year 2011were used to assess the role of District Level Seed Self Sufficiency Program and Community Based Seed Production program on current seed supply situation in Nepal. DISSPRO is the most popular, widely adopted and cheapest seed producing program with annual production of 40.4% followed by CBSP 3.83% of the total certified/improved seeds in the country. The seed production trend of DISSPRO and CBSP is rapidly increasing. Strengthening seed sector through the integration of DISSPRO, CBSP and other seed initiatives together with effective enforcement of seed regulation for quality seed multiplication, distribution and use is necessary for rapid rise on SRR, enhancing crop production and food security in Nepal. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 53-59 DOI: http://dx.doi.org/10.3126/aej.v13i0.7588